The diagnostic and prognostic value of antithrombin III activity for sepsis-induced coagulopathy in septic patients: a prospective observational study - Li, Yuting; Zhang, Feng; Li, Hongxiang; Fu, Yao; Chen, Yumeng; Wang, Youquan; Zhang, Dong (Frontiers in Medicine, 2025)
BackgroundThere are currently no suitable biomarkers for early diagnosis and prognostic evaluation of sepsis-induced coagulopathy (SIC), therefore, studying the diagnostic and prognostic value of antithrombin III (AT-III) activity in SIC may be useful for early identification and intervention of SIC.MethodsThis study is a single-center cohort study, prospectively enrolling patients with sepsis admitted to the ICU from March 2023 to March 2024. Based on whether the SIC score was greater than or equal to 4, the enrolled sepsis patients were divided into the SIC group and the non-SIC group. The SIC scoring system consists of three parameters: International normalized ratio (INR), platelet count, and Sequential Organ Failure Assessment (SOFA) score. The measurement of AT-III activity was completed within 12 h of the patient being admitted to the ICU. The receiver operating characteristic (ROC) curve analysis and area under the ROC curve (AUC) were used to evaluate the accuracy of different biomarkers in the diagnosis and prognostic assessment of SIC. The DeLong Test was employed to compare whether there was a significant difference between AUCs. Kaplan-Meier survival curve was plotted and Log-rank test was performed to compare the 28-day survival rates among different groups.ResultsThis study included a total of 366 patients with sepsis, among which 235 (64.2%) were in the SIC group and 131 (35.8%) were in the non-SIC group. The AT-III activity in the SIC group was significantly lower than that in the non-SIC group (P < 0.001). ROC curve analysis showed that the AUC for AT-III activity was 0.799 (P < 0.001), the AUC for platelets was 0.806 (P < 0.001), the AUC for Sequential Organ Failure Assessment (SOFA) score was 0.746 (P < 0.001), and the AUC for international normalized ratio (INR) was 0.765 (P < 0.001). The results of the DeLong Test showed that the AUC for AT-III activity in diagnosing SIC had no statistically significant difference compared with the AUCs of the traditional diagnostic indicators, including platelets, SOFA score, and INR (P > 0.05). The cut-off value of AT-III activity for diagnosing SIC is 59.7%, with a sensitivity of 79.91%, specificity of 69.77%, positive predictive value (PPV) of 82.59%, and negative predictive value (NPV) of 65.94%. There was no statistical difference in AT-III activity between the survival and non-survival groups of SIC patients (P > 0.05). The proportion of shock and the duration of vasopressor use were both lower in the high AT-III group (≥ 59.7%) than in the low AT-III group < 59.7%) (P < 0.05). Kaplan-Meier survival curves showed that there was no statistically significant difference in the 28-day survival probability between the high AT-III group and the low AT-III group (P = 0.350).ConclusionAT-III activity is a potentially helpful adjunctive biomarker for diagnosing SIC that performs similarly to the biomarkers and scores currently used to diagnose SIC.